Knowledge of self-care among type 2 diabetes patients in Hospital Seberang Jaya - Zamree, Lukhman Nul Hakim; Azizi, Mohammad Hafeez (2018)
Research background: Uncontrolled blood glucose in Type 2 diabetes mellitus (T2DM) is known to cause devastating complications such as blindness, kidney failure, cardiovascular diseases and lower limb amputation. Patient-driven self-care activities performed outside of clinic settings are essential to achieve good glycaemic control. To date, the extent of diabetes self-care knowledge among patients attending Hospital Seberang Jaya remains scare.